A Paper‐Based Platform for Long‐Term Deposition of Nanoparticles with Exceptional Redispersibility, Stability, and Functionality. (5th April 2019) - Cho, Hui Hun; Kim, Su Ji; Jafry, Ali Turab; Lee, Byoungsang; Heo, Jun Hyuk; Yoon, Seokyoung; Jeong, Sun Hwan; Kang, Seong‐Il; Lee, Jung Heon; Lee, Jinkee
Abstract: Although nanoparticles (NPs) can be carefully engineered to have maximal stability and functionality desirable for use in diverse applications, they are generally not suitable for long‐term storage in solution. It is also difficult to store NPs in a dry state because dried NPs generally become aggregated and cannot easily be redispersed. Thus, a new strategy allowing long‐term storage of NPs with high stability, redispersibility, and functionality is highly demanded. By passivating the 13 nm gold nanoparticle (AuNP) surface with stabilizing agents and treating a paper substrate with both bovine serum albumin and sucrose after coating with a hydrophobic polyvinyl butyral layer, it is possible to fully redisperse (≈100%) dried AuNPs with colloidal stability comparable to that of as‐prepared AuNPs. Furthermore, AuNPs physically stabilized with polyvinylpyrrolidone can react with thiol‐containing compounds, such as 1, 4‐dithiothreitol (DTT). Taking advantage of the oxidation reaction of hypochlorous acid with DTT, it is possible to demonstrate a paper‐based colorimetric sensor for detection of residual chlorine in water. Since this strategy is applicable to large‐sized AuNPs (30–90 nm), silver NPs, oleic acid‐capped magnetic NPs, and cetrimonium bromide‐passivated gold nanorods, it can be used for diverse NPs requiring long‐term storage for many applications. Abstract : A new paper‐based platform is reported for the preparation of diverse nanoparticles with exceptional redispersibility, long‐term storage stability, and functionality. It is possible to fully redisperse (≈100%) dried nanoparticles with different compositions, sizes, shapes, and surface capping agents. Gold nanoparticles can be storable at least 6 months and applicable to colorimetric sensor for detection of residual chlorine in water.